Reviews of environmental contamination and toxicology volume 226 - Whitacre, David M. (Reviews of Environmental Contamination and Toxicology, Continuation of Residue Reviews, 2013)
Contents Foreword Preface Current Approaches for Mitigating Acid Mine Drainage Prafulla Kumar Sahoo, Kangjoo Kim, Sk Md Equeenuddin, Michael A Powell Urban vs. Rural Factors that Affect Adult Asthma Yu Jie, Zaleha Md Isa, Xu Jie, Zhang Long Ju, Noor Hassim Ismail Mercury in the Atmospheric and Coastal Environments of Mexico Jorge Ruelas-Inzunza, Carolina Delgado-Alvarez, Martín Frías-Espericueta, Federico Páez-Osuna Do Cd, Cu, Ni, Pb and Zn Biomagnify in Aquatic Ecosystems? Rick D. Cardwell, David K. DeForest, Kevin V. Brix, William J. Adams Index